DELETION WILL BE MY EPITAPH: JOURANLISTS DELETION PRACTICES ON TWITTER - Ringel, Sharon; Davidson, Roei (AoIR Selected Papers of Internet Research, 2020)
This study seeks to understand the practice of the deletion of tweets by journalists while arguing that these uniquely reflect the contemporary fragility of archiving and journalism – two human enterprises central to societies’ ability to reflexively consider the past and present and democratically chart a future course. From the perspective of journalism as a profession, it argues that the study of tweet deletion is a means of examining the constraints under which journalists operate today including the occupational precarity and polarized public sphere with which they contend. From the web archival perspective, this study methodologically informs scholars who are relying on public tweets as a source for their research as well as other social actors – such as NGOs, activists, politicians, cultural producers – who rely on social media as a web archive in their public activities. It proposes to identify some of the voices that will be removed from this public square as it becomes a public archive and highlights the proactive ephemerality of journalistic social media content. Based on interviews conducted in the winter of 2019 with 17 journalists working in New York City, the study examines how journalists perceive the action of deleting their tweets and how they justify it.